If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2(2x + -3) = 10x Reorder the terms: 4x + -2(-3 + 2x) = 10x 4x + (-3 * -2 + 2x * -2) = 10x 4x + (6 + -4x) = 10x Reorder the terms: 6 + 4x + -4x = 10x Combine like terms: 4x + -4x = 0 6 + 0 = 10x 6 = 10x Solving 6 = 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 6 + -10x = 10x + -10x Combine like terms: 10x + -10x = 0 6 + -10x = 0 Add '-6' to each side of the equation. 6 + -6 + -10x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -10x = 0 + -6 -10x = 0 + -6 Combine like terms: 0 + -6 = -6 -10x = -6 Divide each side by '-10'. x = 0.6 Simplifying x = 0.6
| 4(3)-2(-2(3)-3)=10(3) | | -x^3+25x=0 | | 6x^2-6-12=0 | | -4x-6+x=-2x+6+10 | | 3x-1-4x=2x+7x-4 | | 3x-1-4x=2x | | 5x+8-12=6x-2x+3 | | 12x^3y-10x^2y^2-12xy^3=0 | | -3(5-15n)=15(3n-21) | | P^2-10p+22=0 | | r^2+3r-40=0 | | 3x-5y+8-2x+7y= | | .05x^2+2x+2=p | | -50h^3+60h^2y-18hy^2=0 | | 64c^2-144cp+81p^2=0 | | 5x^2+50x+125=0 | | 5x^2+50x+120=0 | | 3x^2-12x+39= | | 11x+2y=812 | | K+k+k+k+k= | | B+17= | | 7+x5= | | 2x^2-6x-20= | | 10x^2=3x | | -2x+5+6x-8= | | 8h^2-18hj-5j^2=0 | | 4x^2+20x=-29 | | 6L=.8L^2 | | -20z^2+7z+3=0 | | 3(x+1)=8(x-1)+5 | | 15d^2+33d-36=0 | | 6(p-3)-3(4-3p)=25+4p |